Product information and its cohesion mechanisms in technical communication - Będkowska-Obłok , Marzena (Papers in Linguistics, 2024)
Technology is a special field of science that combines many other fields, thus forming a unique set of features that are brought into the communication process by its participants, who represent their disciplines, fields of interest or traditions. The article concerns text as used in specialized communication along with its most significant aspect, i.e. its function, since specialized texts are, by definition, independent of their author’s style or way of thinking. The undertaken analysis includes the issue of mechanisms used to ensure textual cohesion and is intended to contribute to research in the field of specialized text linguistics, particularly techno-linguistics. The article analyses cohesion markers which constitute the linguistic means used to guarantee cohesion of a specialized text, i.e. – in this instance – product information. The aim of the study is to scrutinise text cohesion in the analysed genre, it being the result of both the meaning of the text as well as its formal features. The research is based on the commercial offer of household appliances (the so-called white goods) produced by leading German companies.